Impact on parasitemia, survival time and pro-inflammatory immune response in mice infected with Plasmodium berghei treated with Eleutherine plicata - Quadros Gomes, Antônio Rafael; Castro, Ana Laura Gadelha; Ferreira, Gleison Gonçalves; Brígido, Heliton Patrick Cordovil; Varela, Everton Luiz Pompeu; Vale, Valdicley Vieira; Carneiro, Liliane Almeida; Dolabela, Maria Fâni; Percario, Sandro (Frontiers in Pharmacology, 2024)
In vitro studies with Plasmodium falciparum have demonstrated the antiparasitic activity of Eleutherine plicata, attributed to its naphthoquinones. This study reports on pro-inflammatory changes in mice infected with Plasmodium berghei and correlates these changes with parasitemia and survival. The ethanol extract of E. plicata (EEEp) was fractionated under reflux to obtain the dichloromethane fraction (FDMEp) and isolated compounds from E. plicata, relating these to survival time and parasitemia. Antimalarial activity was evaluated using the Peters suppressive test, with mice infected with P. berghei and treated with E. plicata, assessing parasitemia and survival over 30 days. The proinflammatory profile was determined by measuring cytokines and nitric oxide levels. EEEp, FDMEp, and eleutherol showed activity on the 5th day of infection, with only FDMEp being active on the 8th day. Treatment with EEEp and FDMEp extended animal survival, reduced IFN-γ and NO levels, and increased IL-10 levels. Eleutherol significantly altered the response, with eleutherol glucuronide seemingly active by binding to lactate dehydrogenase, inhibiting hemozoin metabolism, leading to parasite death. Pro-inflammatory changes did not appear to correlate with survival and reduced parasitemia. In summary, FDMEp and eleutherol reduced parasitemia, extended survival, and modulated the inflammatory response. FDMEp and eleutherol are promising candidates for developing new antimalarial drugs.